Modern peculiarities of lectures in clinic discipline for english-speaking students - Yaroshevskaya, Tatyana (ScienceRise: Pedagogical Education, 2020)
The aim of the study is the improvement of the modern lecture content in clinical discipline Pediatric Propaedeutics for the foreign students with English language of study. Bibliographic, descriptive methods are used in the research, students are anonymously questioned; processing of the obtained results is carried out by methods of mathematical statistics. Based on our own experience in teaching the discipline Pediatric Propaedeutics, we have created the lecture content for the English-speaking foreign students at the department. Well-structured, well-prepared multimedia lectures with a well-established audience feedback mechanism and extensive use of illustrative materials is in the base of this content. According to the standpoint about a student-centered teaching, the students’ opinion of the quality of lectures and ways to improve them is a subject to careful study. According to the questionnaire, among 185 surveyed students, 84.9% rate the quality of lectures on a five-point scale as "5" or "4", 13.5% rate it as "3". 90.8% of the respondents name the lectures as interesting and useful, but 27.6% of the surveyed students say that they do not consider the lectures to be a necessary form of study. The most frequently interviewed students make suggestions to increase the amount of illustrative material, to give an opportunity to use lectures during independent preparation and to allow free attendance of lectures. Considering the previous positive experience of placing a text-based version of lectures on the site of the department, posting on the site a full package of multimedia lectures may be useful. Lectures are a well-studied methodical form of classes, but the issues of the organization of lectures remain relevant. The results of the questionnaire of students about the quality of lecture at the department indicate a positive assessment of the majority of respondents. Ways to improve the lecture content are careful methodological and technical support of lectures, the use of innovative technologies. It is advisable to place multimedia lectures on the site of the department for independent work of students